PENGARUH PARTISIPASI PEGAWAI, PERUBAHAN SIKAP SETELAH PELATIHAN DAN TENAGA PELATIH TERHADAP KINERJA PEGAWAI DIMODERASI KEDISIPLINAN PEGAWAI DI UNIT PRODUKSI DI PT. SINARMAS OLEOCHEMICAL MEDAN - Mustar Antonius Silalahi (University of Riau Kepulauan, 2020)
This research aims to analyze the impact of employee participation, employee attitude changing after training, and trainer on employee performance where the disciplinary variable is a moderating variable. The problem’s formulation in this research is: Does the participation of employees, changes in employees and trainers influence the performance of employees who were moderated by discipline in PT. Sinarmas Oleochemical Medan. To answer the research question, the research design used is a quantitative survey. The analysis method used is SEM Method by using Partial Least Square (PLS). The result of this research showed that employee participation, employee changing and trainer have a positive effect on employee performance but discipline variable as moderation does not affect employee performance. This research contribution expected to improve employee capability in creating good performance.